Navigating Academic Pursuits in the Middle East: Insights for Indonesian Muslim Students - Maspul, Kurniawan Arif (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
This study provides information for Indonesian Muslim students who want to study in the Middle East. The Middle East is a major hub of Islamic knowledge, with a rich Islamic culture, customs, and teachings. Studying in this location allows students to expand their grasp of Islamic ideas and values, connecting theoretical and practical applications in their daily lives. The Middle East is known for its renowned scholars who provide hands-on learning experiences and mentorship, contributing to intellectual and spiritual growth. Students also benefit from substantial academic resources such as famous universities, libraries, and Islamic literature and manuscripts collections. This presentation's technique included considerable research, personal experiences, and encounters in Jordan, Egypt, and Turkey. The goal is to motivate and encourage Indonesian Muslim students to pursue their academic goals. In the end, seeking knowledge in the Middle East necessitates determination, endurance, cultural adaptation, and a dedication to personal and spiritual growth. The provision of free education and scholarships in the Middle East emphasizes the significance of education as a fundamental human right, with countries trying to increase access and create a more equitable society. Students must stay connected to their roots, seek guidance, and embrace opportunities to become their best version.